Predyspozycje i możliwości zatrudnienia a motywacja wyboru kierunku studiów przez studentów nauk humanistycznych Uniwersytetu Rzeszowskiego i nauk ścisłych Politechniki Rzeszowskiej - Chodkowski, Zbigniew (Kultura-Społeczeństwo-Edukacja, 2021)
Motivation accompanies various human activities from an early age. The basic ones include fun, education and work. These activities are combined in different proportions and depend on the living environment and the interests of the individual. Care, upbringing, family environment and family atmosphere shape the child’s perceptions of the world. These factors also affect the individual in terms of making important decisions, which include undertaking education in a university. The human environment, objects, and the same places also imply various motives in creating human behaviour that translates into aspirations to achieve different life goals. The article is an attempt to present the impact of humans’ predispositions in their fields of interest, their self-assessment of intellectual possibilities, prospects for high -level earnings, employment opportunities in the country and abroad, as well as the curriculum covering subjects that were not difficult in high school and in which the pupil was good on the motives for choosing a major study of students of humanities at the University of Rzeszów and students of exact sciences from Rzeszów University of Technology.